Dog man [videorecording (Blu-Ray)] - Pilkey, Dav, 1966-; Hastings, Peter (Dreamworks, 2025)
Dog Man, half dog and half man, he is sworn to protect and serve as he doggedly pursues the feline supervillain Petey the Cat.